2005
DOI: 10.1111/j.1469-8137.2005.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonates and Na‐orthovanadate promote resveratrol production in Vitis vinifera cv. Barbera cell cultures

Abstract: Summary• Here the effect of jasmonic acid, methyljasmonate and Na-orthovanadate on the production of resveratrol was studied in Vitis vinifera cv. Barbera cell suspension cultures.• Na-orthovanadate at 0.1 m M and 1 m M concentration was efficient in promoting the production and/or accumulation and release in the culture medium of cisresveratrol while trans -resveratrol levels were not affected by this treatment.• Methyljasmonate was highly effective in stimulating both trans -and cis -resveratrol endogenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 42 publications
11
130
1
1
Order By: Relevance
“…There are multiple studies showing that stilbene production in cultivated grapevine and grapevine cell cultures increased after treatments with JA or MeJA (Larronde et al 2003;Tassoni et al 2005Tassoni et al , 2012Vezzulli et al 2007;Kiselev et al 2007;Faurie et al 2009;Taurino et al 2015;Xu et al 2015;Degu et al 2016). The effects of 12-oxophytodienoic acid (OPDA), a biologically active JA precursor, and coronatine (COR), a fungal phytotoxin mimicking the biologically active form of JA (JA-Ile), on stilbene biosynthesis have been investigated using cell suspension cultures of V. vinifera and compared with that effects of JA and MeJA (Taurino et al 2015;Almagro et al 2015).…”
Section: Hormonal Regulation Of Stilbene Biosynthesismentioning
confidence: 99%
“…There are multiple studies showing that stilbene production in cultivated grapevine and grapevine cell cultures increased after treatments with JA or MeJA (Larronde et al 2003;Tassoni et al 2005Tassoni et al , 2012Vezzulli et al 2007;Kiselev et al 2007;Faurie et al 2009;Taurino et al 2015;Xu et al 2015;Degu et al 2016). The effects of 12-oxophytodienoic acid (OPDA), a biologically active JA precursor, and coronatine (COR), a fungal phytotoxin mimicking the biologically active form of JA (JA-Ile), on stilbene biosynthesis have been investigated using cell suspension cultures of V. vinifera and compared with that effects of JA and MeJA (Taurino et al 2015;Almagro et al 2015).…”
Section: Hormonal Regulation Of Stilbene Biosynthesismentioning
confidence: 99%
“…One of these strategies is the use of elicitors, particularly jasmonic acid and its derivative, methyl jasmonate, which are signal molecules able to increase plant defense responses such as the production of secondary metabolites (Tassoni et al 2005;Almagro et al 2014;Kastell et al 2013a;Alvarez et al 2008). In this sense, Alvarez et al (2008) observed that the treatment with methyl jasmonate provoked an increase of total levels of glucosinolates, and the response was dependent on the age of cell culture.…”
Section: The Addition Of Elicitors To Improve the Bioproduction Of Glmentioning
confidence: 99%
“…Almagro et al, (2010) demonstrated that the maximum level of ajmalicine produced by cells and secreted to the media was reached when cell suspensions were incubated in the presence of MJ and CDs, production being around 2.2-fold higher than when cells were treated only with CDs. Moreover, Tassoni et al, (2005) showed that MJ was highly effective in stimulating endogenous trans-resveratrol accumulation, as well as promoting its release into the extracellular medium of V. vinifera cv Barbera cell cultures. In this case, the endogenous trans-resveratrol accumulation was around 24 µg/g dry weight (DW) and the transresveratrol secreted to the medium was over 8 µg/g DW.…”
Section: Wwwintechopencommentioning
confidence: 99%